Digital generation through the prism of culture (Journal of Philosophy Culture and Political Science, 2018)
The global computer network created a virtual reality that replaced the real space of man. The new network has created communication platforms, thanks to which the young generation has the opportunity to interact with each other from any part of the globe. The spread of digital technologies has created the notion of digital space, and people (mostly young in age) concept – the digital generation, or the Google-generation. For the first time the concept of digital generation was given by the teacher M. Prenskyin 2000, describing a new phenomenon. M. Prensky argues that the new generation is radically differentfrom previous generations, and J. Palfrey and C. Gasser believe that the identity of the Z generationis presented in several spaces at once: in digital and real. Numerous researches of foreign and Russianauthors concern pedagogical and psychological aspects of studying the network generation. The noveltyof this work is to try to study the digital generation through culture and its space. The article is devotedto the study of the phenomenon “Generation Z”, “Generation of Digital Aborigines”, “Network Generation”.These word combinations are used in relation to the generation born in 2000 to the present, inconditions of active use of digital technologies. The authors consider the main directions of research onthe problems of the digital generation, based on the concept of the theory of generations of N. Howe andW. Strauss. The article analyzes the views of researchers on the concept of “cultural space”, the authorsproposed their understanding of the cultural space of the digital generation, which is primarily related tomedia culture. For the first time, the criteria for the cultural space of the digital generation are defined,the problem of self-identification and value orientations of the digital generation is raised. When studyingthe phenomenon of the digital generation, methods of a theoretical level are used.This problem hasbeen underexplored and requires further research. Quite an interesting field of study for cultural studies,psychologists, neuroeconomists, marketers, experts in youth policy and education.Key words: cultural space, media culture, digital generation, digital technologies.